2007
DOI: 10.1093/eurpub/ckm036
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol drinking, consumption patterns and breast cancer among Danish nurses: a cohort study

Abstract: For alcohol consumption above the intake most frequently reported, the risk of breast cancer is increased. The risk is minor for moderate levels but increases for each additional drink consumed during the week. Weekend consumption and binge drinking imply an additional increase in breast cancer risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 21 publications
1
29
0
1
Order By: Relevance
“…The few studies that have previously evaluated binge drinking have reported positive associations between current binging and breast cancer, with binging being defined as consuming more drinks over the weekend (22) and as ever drinking ≥6 drinks/day in a typical month (21). One case-control study also found effect-measure modification of current alcohol consumption by current binge drinking status, with elevated risk limited to the highest category of drinkers (≥91 g/week) who also reported binging (defined as 5 or more drinks in one sitting) (23).…”
Section: Discussionmentioning
confidence: 99%
“…The few studies that have previously evaluated binge drinking have reported positive associations between current binging and breast cancer, with binging being defined as consuming more drinks over the weekend (22) and as ever drinking ≥6 drinks/day in a typical month (21). One case-control study also found effect-measure modification of current alcohol consumption by current binge drinking status, with elevated risk limited to the highest category of drinkers (≥91 g/week) who also reported binging (defined as 5 or more drinks in one sitting) (23).…”
Section: Discussionmentioning
confidence: 99%
“…10, 11 In terms of binge drinking, a prospective study showed a non-linear association with the highest risk among those who consumed 4-5 drinks per weekday or 16-21 drinks per weekend and lower risks for those who drank more, but they had few cases in the highest categories and contrary to most studies, non-drinkers had an increased risk of breast cancer. 33 A case-control study found a non statistically significant increased risk associated with binge drinking limited to high alcohol consumers. 34 After controlling for cumulative average intake, we observed an association with binge drinking, but not frequency of drinking.…”
Section: Discussionmentioning
confidence: 99%
“…However, alcohol consumed between menarche and the first pregnancy (among parous women) has been associated with an increased risk of proliferative benign breast disease and breast cancer . Patterns of alcohol consumption are also hypothesized to modify the risk relationship between alcohol consumption and breast cancer; however, only a few drinking pattern studies exist (irregular heavy drinking occasions; see Rehm et al, 1996) and epidemiological evidence on this effect modification is limited and inconsistent (Chen et al, 2011;Horn-Ross et al, 2004;Jeffreys et al, 2013;Lash and Aschengrau, 2000;Mørch et al, 2007;Tjønneland et al, 2007).…”
Section: Discussionmentioning
confidence: 99%